Investigating the usage of unsaturated fatty acid-rich and low-calorie oleogels as a shortening mimetics in cake - Pehlivanoglu, Halime; Ozulku, Gorkem; Yildirim, Rusen Metin; Demirci, Mehmet; Toker, Omer Said; Sagdic, Osman (WILEY, 2018)
In the present study, two purposes were aimed: (a) Reduction of fat content of cakes using watery oleogels and (b) Reduction of saturated fatty acid contents of cakes using oleogels rich in unsaturated fatty acid composition instead of shortening. For this aim, five different oleogels were produced using different percentages of high oleic sunflower oil, cotton seed oil, and blend fat and they were used in the cake formulation instead of shortening. Some physicochemical properties of oleogels (solid fat content and fatty acid composition) were determined. Specific volume, color, textural, and sensory properties of cakes containing prepared oleogel were also analyzed and compared to those of control sample. In addition, rheological properties of the batters were also determined. Color properties of the oleogel-containing cakes were found to be very similar to those of control sample. Oleogel formulation significantly affected the textural characteristics. Sensory scores showed that cakes including oleogels were found to be consumable level and the most acceptable sample was detected as the one including oleogel which was produced from high oleic acid sunflower oil and cotton seed oil at equal amounts (50/50). The results indicated that oleogels could be used in the formulation of cakes as a shortening replacer; thus, it might be possible to produce cakes rich in unsaturated fatty acids and cakes with lower calorie value, which is important for consumer acceptability of the products. Practical applicationOleogels are novel system produced by solidifying liquid oils by using oleogelators and have great potential for food industry. Using oleogels in food formulations allows to manufacture products that contain low amount of saturated fatty acid, which protect human health, especially against cardiovascular diseases. Moreover, oleogels have been used in different food formulations such as cookies, meat products and cheese etc. In the present research, water based-wax oleogels were used in the cake formulation instead of shortening and, findings showed that wax oleogels had not any reverse effect on the quality of food product. Also, due to low saturated fatty acid content of oleogels, many healthy food products could be produced using oleogels. On the other hand, as manufacturing process of oleogels is not that difficult, large amount of production could be easily achieved.
Keywords: RHEOLOGICAL BEHAVIOR; OIL OLEOGELS; BAKED GOODS; REPLACEMENT; QUALITY; BATTER; WAX; ETHYLCELLULOSE; CHOCOLATE; PRODUCT; Food Science & Technology